2020
DOI: 10.1002/jev2.12029
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles derived from macrophages display glycyl‐tRNA synthetase 1 and exhibit anti‐cancer activity

Abstract: Glycyl‐tRNA synthetase 1 (GARS1), a cytosolic enzyme secreted from macrophages, promotes apoptosis in cancer cells. However, the mechanism underlying GARS1 secretion has not been elucidated. Here, we report that GARS1 is secreted through unique extracellular vesicles (EVs) with a hydrodynamic diameter of 20–58 nm (mean diameter: 36.9 nm) and a buoyant density of 1.13–1.17 g/ml. GARS1 was anchored to the surface of these EVs through palmitoylated C390 residue. Proteomic analysis identified 164 proteins that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…While not discussed in this review, it is important to note that macrophages also secrete EVs within the TME that are able to drive or inhibit tumor progression (Goughnour et al, 2020;Zhang et al, 2020;Chang et al, 2021;Liu et al, 2021;Xavier et al, 2021). This cross-talk between tumors and macrophages, can result in complex paracrine and autocrine circuits that affect disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…While not discussed in this review, it is important to note that macrophages also secrete EVs within the TME that are able to drive or inhibit tumor progression (Goughnour et al, 2020;Zhang et al, 2020;Chang et al, 2021;Liu et al, 2021;Xavier et al, 2021). This cross-talk between tumors and macrophages, can result in complex paracrine and autocrine circuits that affect disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CPT1A plays a crucial role in radioresistant and chemoresistant phenotypes in diverse cancer types [ 41 , 42 , 82 ]. Equally, altered protein levels of FLNA, HSPA7, HGF, ERO1A, and GARS1, have been related to cancer migration, adhesion, poor patient prognosis, and metastasis [ 48 , 49 , 50 , 83 , 84 ]. Particularly, filamin A (FLNA), a cytoskeleton regulator, has been reported as taking on opposite roles depending on the cancer type [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, macrophages are exposed to environmental stresses, such as nutrient deprivation, hypoxia, and the signaling factors, including HSPs, released from cancer cells. These macrophages could recruit diverse intracellular factors and package them into secretory vesicles to mediate the primary response against cancer cells until the immune surveillance system was activated [46]. It was also found that macrophages cultured in glucose-depleted medium secreted human glycyl-tRNA synthetase 1 (GARS1)-EVs, which involved an immunological defense response against tumorigenesis and could promote cancer cell death [46,47].…”
Section: Discussionmentioning
confidence: 99%